Kedudukan Hukum Akta Pengakuan Hutang yang Dibuat Dihadapan Notaris (Studi Kasus Perkara Mahkamah Agung Nomor: 2956/K/Pdt/2013) - Puspita Siregar, Elvia; Danil, Elwi; Fendri, Azmi (Universitas Ekasakti, 2023)
A deed of acknowledgment of debt made by a notary authentically will be followed by a deed of acknowledgment of debt also authentically made by a notary. If the debtor is in default in carrying out his obligations to the creditor, based on the debt acknowledgment deed a grosse deed can be issued, which is the first copy which has the same force as a court decision which has permanent legal force. In this research, the formulation of the problem related to the legal protection of Land Deed Drafting Officials (PPAT) against acts of falsification of data on sale and purchase deeds by applicants, namely: 1. What is the legal position of the Deed of Debt Acknowledgment made before a Notary in Supreme Court case Number 2956 K/Pdt/2013 ? 2. What is the judge's consideration in Supreme Court case Number 2956.K/PDT/2013 in relation to the Deed of Debt Acknowledgment made to the Notary? 3. What are the legal consequences of the decision of Supreme Court case Number 2956.K/Pdt/2013 on the Deed of Debt Acknowledgment made before a Notary? This research uses a juridical-normative approach. The research results obtained are: normative legal research, namely research. The results of the discussion of the problems that arise in this research are that the legal strength of a debt acknowledgment deed made by a notary with an authentic deed is perfect evidence for parties in the event of prosecution in court. Apart from that, the deed of acknowledgment of debt made by the notary is authentically legally binding in accordance with the law for the parties who make it so that it must be adhered to, complied with and implemented as well as possible and in good faith to achieve the smooth implementation of the debt. The legal consequence of making a debt acknowledgment deed made by a notary against the parties in the event of a trial in court is that the parties are bound by a debt payment agreement which they have acknowledged using an authentic notarial deed in the form of a debt acknowledgment deed. The basis for the legal considerations of the panel of judges in deciding the case of a lawsuit for cancellation of a debt acknowledgment deed made by a notary with an authentic deed in Supreme Court Decision No. 2956.K/PDT/2013 is that the cassation filed by Defendant I HH and Defendant II DH does not have strong reasons or does not have a strong legal basis to be submitted to the Supreme Court. However, the clause of the debt acknowledgment deed made by the notary containing the provisions for interest/late fines of 8% (eight percent) per month was canceled by the panel of judges and changed to 2% (two percent) per month because the interest provision was 8% (eight percent). per month, the legal provisions in force in the banking law require that the interest rate on a loan must not exceed 2% (two percent) per month.?